Compost Production from Olive Tree Pruning Wastes Enriched with Phosphate Rock. Issue 1 (2nd January 2017) - Ghoneim, A. M.; Elbassir, O. I.; Modahish, A. S.; Mahjoub, M. O.
ABSTRACT: Olive production is increasing very fast in the last 20 years in Al-Jouf region, northern region of the Kingdom of Saudi Arabia. There are now more than 5 million olive trees in the productive stage. A huge amount of waste is produced annually from this sector, including pruning waste of olive trees and solid waste from olive oil mills of three-phase system. The waste of olive used to produce compost could be of safe disposal technique. Disposal of such waste is expensive and it causes some environmental hazards. Rock phosphate (RP), which is available in the same region, can be used to improve the nutrient value of the produced compost. In this experiment olive pruning waste was composted alone and in a mixture with different RP in two different ratios, namely 5% and 10%, on the dry weight basis of olive waste. Compost processing took place on plies for 8 months. Temperature and moisture were monitored daily while periodical samples were taken from all piles for testing pH, EC, C/N, and germination index. Composts in all treatments reached the theomorphic phase, which killed weed seeds and pathogens. The produced compost from all treatments fulfilled the requirements of maturity according to the California Compost Quality Council after 8 months of composting. In addition, the RP enhanced composting efficiency and improved the quality of the produced compost. Compost parameters met the standard requirements for the compost that was suitable for agriculture purposes with average values of pH ranging from (7.02–7.65) and EC (2.20–3.94 dS m −1 ). Nutrient concentrations in the produced compost were N (1.28–1.79%), P (0.23–2.15%), and K (2.59–4.22%).